Effects Of Surfactant-Based Warm Mix Additive On Adhesive Failure And Moisture Damage Of Asphalt Mixtures Using Imaging Technique - Teh, Sek Yee (2018)
The incorporation of Warm Mix Asphalt (WMA) technology allows reduction in production and placement temperatures of conventional Hot Mix Asphalt (HMA). It is not only a cost effective technology that enhances mixture workability, but it also lowers greenhouse gas emissions and is environmentally friendly. However, the destructive effects of moisture remain to be the main concern influencing WMA performance owing to its lower production temperatures. This can consequently result in adhesive failure, hence stripping of asphalt binder and mastics from aggregates. In this research, the Evotherm warm mix additive was incorporated to lower the production temperature and improve adhesive strength at the asphalt-aggregate interface. The PG-64 and PG-76 binders were used in the preparation of test specimens. As a surfactant-based and adhesion promoter additive, Evotherm enhances the adhesive properties of asphalt binder with aggregate. Thus, the overall laboratory results demonstrated that addition of Evotherm had insignificant effects on binder rheology. An innovative approach using 2-D and 3-D imaging techniques was used to quantify the adhesive failure susceptibility of direct and indirect tensile tests specimens due to moisture damage. The results showed that percentage adhesive failure increased with increasing Freeze-Thaw (F-T) cycle and PG-76 mixtures exhibited lower percentage adhesive failure than PG-64 mixtures. To further quantify adhesive failure, the asphalt-aggregate substrate and pull-off tensile tests were carried out. A novel approach was adopted to expose asphalt-aggregate substrate specimens to various combinations of aging and moisture conditioning to evaluate their adhesive strength. This approach realistically simulated the actual field pavement conditions. An accelerated laboratory vacuum saturator (ALVS) moisture conditioning was employed to condition the asphalt-aggregate specimens. The results implicated that specimens subjected to combined long-term aging and moisture conditioning were more susceptible to moisture damage. Specimens using limestone showed better affinity towards binder and mastics demonstrated by the higher tensile strength and lower percentage adhesive failure than granite specimens. Mixtures moisture damage and rutting resistance were also further evaluated using the dynamic creep and wheel tracking tests. Mixtures moisture susceptibility was assessed in terms of stripping phase slope and stripping inflection point (SIP), while mixtures rutting resistance was quantified in terms of creep phase slope, mean rut depth and dynamic stability. Moisture damage evaluations showed that Evotherm improved the moisture susceptibility of WMA compared to HMA particularly for mixtures prepared at higher compaction temperatures. The WMA compacted at higher temperatures also exhibited comparable rutting resistance with HMA, regardless of binder type.